CCAFS. 1st Independent Science Panel Meeting, Cali, Colombia, 11–14 November 2011 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
In November 2011 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its first Independent Science Panel meeting in Colombia.